2014
DOI: 10.1007/s10439-014-1058-9
|View full text |Cite
|
Sign up to set email alerts
|

Short Duration Electrical Stimulation to Enhance Neurite Outgrowth and Maturation of Adult Neural Stem Progenitor Cells

Abstract: New therapies are desperately needed for human central nervous system (CNS) regeneration to circumvent the lack of innate regenerative ability following traumatic injuries. Previously attempted therapies have been stymied by barriers to CNS regeneration largely because of protective mechanisms such as the blood brain barrier, inhibitory molecules, and glial scar formation. The application of electric stimulation (ES) has shown promise for enhancing peripheral nervous system regeneration, but is in its infancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 46 publications
1
40
0
1
Order By: Relevance
“…Notwithstanding the need to further investigate the interaction between the insulating layer and cells presently used, any putative negative effects were resolved by ES. Our findings are in keeping with other reports of the effects of ES on rate and fate determination of differentiating NSCs, including our own research, albeit it through the use of CP films for 2D planar ES rather than 3D ES of tissues presently described …”
supporting
confidence: 92%
See 1 more Smart Citation
“…Notwithstanding the need to further investigate the interaction between the insulating layer and cells presently used, any putative negative effects were resolved by ES. Our findings are in keeping with other reports of the effects of ES on rate and fate determination of differentiating NSCs, including our own research, albeit it through the use of CP films for 2D planar ES rather than 3D ES of tissues presently described …”
supporting
confidence: 92%
“…Cellular responses include galvanotaxis, increased intracellular calcium concentration, extracellular matrix assembly, and associated cell proliferation and differentiation . Several recent reports have shown that electrical stimulation (ES) can be used to modulate fate determination of differentiating human neural stem cell (NSCs), including the promotion of neuronal versus glial cell induction and increased neuritogenesis . From our own research, we have demonstrated the use of biphasic electrical current via a conductive polymer (CP), polypyrrole, to promote neurite outgrowth and synaptogenesis of rat primary cortical neurons, as well as differentiation of human NSCs to neurons with longer neurites and increased branching, and concomitant lower induction of neuroglia …”
mentioning
confidence: 99%
“…Short duration electrical stimulation at physiological level (0.53 or 1.83 V/m) was effective in enhancing neurite outgrowth and maturation of adult neural stem progenitor cells [25]. Ariza et al [26] found that the NPCs treated with a 437 V/m direct current (DC) EF aligned perpendicularly to the field vector had a greater tendency to differentiate into neurons, but not into oligodendrocytes or astrocytes, compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has not been investigated how an applied EF may influence the movements of migratory cells such as adult-born spinal neural cells in vivo. An applied EF also affects cell differentiation, as well as the maturation of isolated adult-born neural cells by causing neural cells to differentiate into neurons, but not glia (11,40). Thus, while the effects of an EF on isolated stem/precursor cells is well established, the effects of an EF on adult-born cells in vivo remain unknown.…”
mentioning
confidence: 99%